A sustainable approach to deep geothermal energy exploitation: feasibility of clustered U-shaped multi-branch wells - Xu, Tao; Li, Shouding; Zhang, Zhaobin; Kong, Yanlong; Zheng, Bo; Ma, Shiwei; Zhang, Supeng; He, Jianming; Li, Xiao (Frontiers in Earth Science, 2025)
To overcome the limitations of unstable heat extraction power and low efficiency in current deep geothermal energy exploitation technologies, we propose a novel and sustainable approach using clustered U-shaped multi-branch wells (UMW). This method enables efficient heat exchange by circulating working fluid through U-shaped wells, where thermal energy is transferred between the working fluid and the reservoir via the wellbore wall, avoiding any material exchange. For the validation of UMW method, based on the high-temperature and high-pressure thermal conductivity tests using hot dry rock samples from the Gonghe Basin, we developed a UMW field-scale reservoir-wellbore coupling model to assess the efficient heat extraction processes and the potential generating power of Organic Rankine Cycle (ORC). The results highlight that high injection rates lead to rapid thermal breakthrough and a sharp decline in early-stage heat extraction power, indicating the need for careful optimization of operational parameters. The average heat recovery power of a single set of six branch wells over a 50-year operating cycle is ∼4.32 MW. The ORC power generation capacity was conservatively estimated at ∼284.4 kW over the first 21.5 years, and ∼144.6 kW over the 50-year period. Sensitivity analysis of injection rates and the number of branch wells further suggests that balancing short-term power and long-term thermal stability requires adjusting injection rates, the number of branch wells, well spacing, and branch well operational schematic. We also provide a partial quantitative relationship between ORC power and operational parameters (injection rate and the number of branch wells) for optimization. This study demonstrates the promising potential of the UMW method for sustainable deep geothermal energy development. Future research will focus on refining quantitative optimization strategies for injection rates and operational cycles to ensure efficient and long-term heat extraction while maintaining system stability.